Hubungan Social Comparison di Instagram dengan Self Esteem Mahasiswa Penerima Beasiswa Prestasi di Universitas Jambi - Nuraini Nuraini; Marlita Andhika Rahman; Ayu Ulivia; Annisa Andriani (Lembaga Pengembangan Kinerja Dosen, 2026)
The massive use of Instagram among university students has given rise to the phenomenon of social comparison, namely the tendency of individuals to compare themselves with the achievements of others displayed on social media. This phenomenon has the potential to affect self esteem, including among student recipients of academic achievement scholarships who face particular academic and social demands. This study aims to identify the relationship between social comparison on Instagram and self esteem among scholarship-recipient students at Universitas Jambi. This study employed a quantitative correlational approach with a cross-sectional design. The research sample consisted of 64 active academic achievement scholarship recipients at Universitas Jambi, selected through purposive sampling technique. Data were collected through questionnaires using the Iowa-Netherlands Comparison Orientation Measure (INCOM) to measure social comparison and the Coopersmith Self Esteem Inventory (CSEI) to measure self esteem. Data were analyzed using Pearson Product Moment correlation technique with the assistance of SPSS version 22. The results showed that the level of social comparison among scholarship-recipient students was in the moderate category (60.9%), and likewise the level of self esteem was also in the moderate category (73.4%). Hypothesis testing results showed a significant negative relationship between social comparison and self esteem (r = -0.386; p = 0.002; p < 0.05), thus the alternative hypothesis (H1) was accepted. This negative relationship indicates that the higher the level of social comparison conducted by students, the lower their level of self esteem, and vice versa. This study concludes that self-regulation of social media use intensity and self-comparison habits is an important factor for academic achievement scholarship recipients in maintaining healthy and stable self esteem.